Heat stroke with bimodal rhabdomyolysis: a case report and review of the literature. Issue 1 (December 2016) - Yoshizawa, Toshihiko; Omori, Kazuhiko; Takeuchi, Ikuto; Miyoshi, Yuto; Kido, Hiroshi; Takahashi, Etsuhisa; Jitsuiki, Kei; Ishikawa, Kouhei; Ohsaka, Hiromichi; Sugita, Manabu; Yanagawa, Youichi
Abstract Background Severe heat stroke tends to be complicated with rhabdomyolysis, especially in patients with exertional heat stroke. Rhabdomyolysis usually occurs in the acute phase of heat stroke. We herein report a case of heat stroke in a patient who experienced bimodal rhabdomyolysis in the acute and recovery phases. Case presentation A 34-year-old male patient was found lying unconscious on the road after participating in a half marathon in the spring. It was a sunny day with a maximum temperature of 24.2 °C. His medical and family history was unremarkable. Upon arrival, his Glasgow Coma Scale score was 10. However, the patient's marked restlessness and confusion returned. A sedative was administered and tracheal intubation was performed. On the second day of hospitalization, a blood analysis was compatible with a diagnosis of acute hepatic failure; thus, he received fresh frozen plasma and a platelet transfusion was performed, following plasma exchange and continuous hemodiafiltration. The patient's creatinine phosphokinesis (CPK) level increased to 8832 IU/L on the fifth day of hospitalization and then showed a tendency to transiently decrease. The patient was extubated on the eighth day of hospitalization after the improvement of his laboratory data. From the ninth day of hospitalization, gradual rehabilitation was initiated. However, he felt pain in both legs and his CPK level increased again. Despite the cessation of all drugs and rehabilitation, his CPK level increased to 105, 945 IU/L on the 15th day of hospitalization. Fortunately, his CPK level decreased with a fluid infusion. The patient's rehabilitation was restarted after his CPK level fell to <10, 000 IU/L. On the 31st day of hospitalization, his CK level decreased to 623 IU/L and he was discharged on foot. Later, a genetic analysis revealed that he had a thermolabile genetic phenotype of carnitine palmitoyltransferase II (CPT II). Conclusions Physicians should pay special attention to the stress of rehabilitation exercises, which may cause collapsed muscles that are injured by severe heat stroke to repeatedly flare up.